Analysis of Survival Curves: Statistical Methods Accounting for the Presence of Long-Term Survivors - Damuzzo, Vera; Agnoletto, Laura; Leonardi, Luca; Chiumente, Marco; Mengato, Daniele; Messori, Andrea (Frontiers in Oncology, 2019)
Not required for Mini-Reviews